Translation, History, Narrative - Venuti, Lawrence (Meta, 2005)
AbstractEvery stage in the production, circulation and reception of a translation is profoundly marked by its historical moment, tracing a history that is distinct from the history of the foreign text. The historical nature of translation is apparent in the succession of varying methods that define it within a single culture, not only standards of accuracy, but the interpretation of the conceptual categories on which that standard is based, not only discursive strategies and the very linguistic texture of translations, but the conceptual discourses that translators inscribe in foreign texts as interpretations. Translation traditions can be sketched in which specific practices are repeatedly performed for decades, centuries, even millennia. The relations between translation universals and norms are subject to historical variation. A history of translation, like any history, endows translation practices with significance through a narrative form or mixture of forms, depending on the factors that the historian selects to describe the chronological succession of practices.